Sustainability in fashion : a cradle to upcycle approach - Henninger, Claudia E.; Alevizou, Panayiota J.; Goworek, Helen; Ryding, Daniella (Palgrave Macmillan, 2017)
This book provides a critical insight into sustainability and fashion in a retailing and marketing context. Examining a truly global industry, Sustainability in Fashion offers international application with a view to contextualising important developments within the industry. Contributors use their diverse backgrounds and expertise to provide a contemporary approach in examining key theoretical concepts, constructs and developments. Topics include consumer behaviour, communications, circular economy and supply chain management. The individual chapters focus on sustainability and provide a range of fashion sector examples from high street to luxury apparel.